2018
DOI: 10.1021/acs.energyfuels.8b03559
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Crumb Rubber Modifiers after Dispersion in Asphalt Binders

Abstract: Blending ground crumb rubber (CR) with the asphalt binder is an economical and sustainable method of binder modification. The objective of this paper was to evaluate the interaction between the asphalt binder and the three CR types at 170 and 190 °C. The three CR types, ambiently ground, cryogenically ground, and Ecorphalt (E-rubber), were blended with a Louisiana conventional PG 67-22 asphalt at two temperatures, 170 and 190 °C. The composition of the CR before and after treatment with asphalt was studied usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…2,3 So many waste tires are bound to put huge pressure on the environment protection. 4,5 Therefore, how to dispose of these waste tires is an urgent problem in many countries, and it has also been a hot research topic for many years. Studies have shown that using the waste rubber to modify the asphalt binders may be an efficient way to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 So many waste tires are bound to put huge pressure on the environment protection. 4,5 Therefore, how to dispose of these waste tires is an urgent problem in many countries, and it has also been a hot research topic for many years. Studies have shown that using the waste rubber to modify the asphalt binders may be an efficient way to solve this problem.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that around 1.5 billion scrap tires are produced each year and the number is still increasing sharply 2,3 . So many waste tires are bound to put huge pressure on the environment protection 4,5 . Therefore, how to dispose of these waste tires is an urgent problem in many countries, and it has also been a hot research topic for many years.…”
Section: Introductionmentioning
confidence: 99%
“…According to Daly et al [44], most of the reported studies on the influence of synthetic crumb According to Wang et al [39], the asphalt-rubber interaction highly depends on time and mixing temperature. Other studies also reported that the use of recycled tire rubber waste in asphalt mixtures lowered thermal susceptibility [2,40], reduced penetration, enhanced the softening point temperature, and, as a result, increased the stability of the asphalt mixtures [41,42].…”
Section: Interaction Effects Of Crumb Rubber-modified Asphalt Bindermentioning
confidence: 99%
“…According to Daly et al [44], most of the reported studies on the influence of synthetic crumb rubbers on asphalt binder have focused on factors such as crumb rubber particle size, rubber concentration, and blending temperature. On the other hand, fewer studies have investigated the effect of rubber composition on asphalt binder properties.…”
Section: Interaction Effects Of Crumb Rubber-modified Asphalt Bindermentioning
confidence: 99%
“…To counteract this phenomenon, several methods aiming to control the swelling behavior of rubber exist. The addition of chemicals to the mixture [13,14], the possible devulcanization [15][16][17][18] or, last but not least, the surface treatment of the CR employing physical or chemical procedures [1,[19][20][21][22][23] are some of the most frequent solutions. The rubber's surface treatment represents an evolving method, preferably used when the dry incorporation method is adopted.…”
Section: Introductionmentioning
confidence: 99%